Effect of Different Processing Methods on Resistant Starch Contents of Selected Rice Varieties - Printhajini, P.; Arasaratnam, V. (University of Jaffna, 2020)
Resistant starch (RS) is considered to possess several health benefits. The content of RS in different varieties of rice in the Northern Province of Sri Lanka and the effect of different traditional methods of processing on RS content were determined. Five commonly consumed rice varieties [two improved (Bg 250 and Bw 351) and three traditional varieties (Periyavellai, Pachchaperumaal and Moddakaruppan)] were selected. Samples were processed by roasting, cooking with and without draining of excess water and cooking the presoaked rice without draining the excess water. The total starch, non-RS and RS contents before and after processing were estimated. The highest and lowest amounts of RS were found in raw Pachchaperumaal (27.87±0.32%) and Bw 351 (18.94±0.26%) varieties, respectively. When roasted, highest and lowest amounts of RS were found in Bw 351 (11.09±1.29%) and Bg 250 (7.32±1.68%), respectively. Further, Bw 351 contained highest amount of RS when cooked without draining the excess water (11.63±1.2%) and with draining excess water (11.40±0.50%). Periyavellai contained lowest amount of RS when cooked without draining the excess water (7.04±0.5%) and with draining excess water (4.45 ±0.60%). Periyavellai contained the highest amount of RS (14.50±0.84%) and Moddakaruppan contained the lowest amount of RS (11.75±0.58%) when the rice was pre-soaked before cooking and without draining the excess water. On the basis of complete randomized design, cooking methods have effect on RS content (p<0.05). The RS contents of raw rice and pre-soaked rice cooked without draining of excess water were significantly different. Different processing methods have significantly reduced the total starch, non-RS and RS contents. As the processed rice is consumed; among the rice varieties and the processing methods, consuming presoaked Periyavellai rice variety cooked without draining excess water could be recommended to have more RS.
Keywords: Resistant starch; Sri Lankan rice varieties; Improved rice varieties; Traditional rice varieties